Missed injuries in combat casualties: Lessons from Iraq and Afghanistan. Issue 5 (May 2019) - Undurraga Perl, Vicente J.; Johnson, Connie; Kelley, Sean; Woods, Pam; Martin, Kathleen; Zonies, David
Highlights: Missed injuries during combat operations occur with low but consistent frequency. Most missed injuries are minor and orthopedic in nature. No deaths have been directly attributable to missed injuries during combat operations. Abstract: Introduction: Once injured in the battlefield in Iraq and Afghanistan, U.S. and NATO troops receive medical treatment through tiered echelons of care with varying resources, from austere to state-of-the-art. Similar to civilian trauma systems, the aim is to provide rapid and safe patient movement toward definitive management. A consequence of the rapid transfer of patients is the possibility of missed or delayed diagnosis of injuries. With the new injury patterns seen during these conflicts, we aimed to identify and characterize which injuries are missed and what consequences do they have on our troops' road to recovery. Patients and Methods: A retrospective review of a PI database (established 2007) for consecutively admitted combat casualties was performed between 2007–2013. Baseline patient characteristics, injury year, admitting service, injury type, and subsequent management decisions were categorized and analyzed. Results: There were 301 missed injuries (MI) identified in 248 patients. The annual missed injury rate was 25 per 1000 admissions. Missed injuries were associated with a penetrating mechanism (82.7% vs 58.5%, p < 0.001), ICU admission (58.5% vs 27.4%, p < 0.001), higher ISS (median 14 vs 8, p < 0.001), and a longer length of stay (median 3 versus 2 days, p < 0.001). 194 (64.5%) missed injuries led to a change in management, with 68 (22.6%) requiring a surgical procedure. 1.3% of missed injuries were life threatening, 28.2% major and 65.4% minor. The most common injuries were distal extremity fractures (23.9%), followed by spine fractures (13.3%) and traumatic tympanic membrane rupture (12.6%), There were no deaths attributed to a missed injury. Discussion: Missed injuries during combat operations occur on a low but consistent basis. Most injuries are orthopedic in nature and typically occur in critically ill patients admitted to the ICU. It is rare that a missed injury results in a life-threatening condition. Conclusion: As healthcare practitioners prepare for future deployments, this analysis may serve as a resource to focus on frequently missed injuries and possibly improve their detection.